1966
DOI: 10.1111/j.1600-0609.1966.tb00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Serum Factors and Prothrombin During Intravascular Clotting in Rabbits

Abstract: We have studied the effect of experimental intravascular clotting upon Factors II, VII, IX, and X in rabbits. Animals were given sodium warfarin intravenously to block the synthesis of these factors and, 4 hours later, were infused with either dilute tissue thromboplastin or saline. The tissue thromboplastin induced intravascular clotting extensive enough to halve fibrinogen and platelet levels and to reduce markedly Factor V and Factor VIII levels. These changes resulted from a consumption during clotting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The observed decrease in factor IX activity during the infusion (Figure 3), which confirms the findings of Rapaport et al (1966), deserves a special comment. Factor IX is probably not activated by thrombin , neither is it con-…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The observed decrease in factor IX activity during the infusion (Figure 3), which confirms the findings of Rapaport et al (1966), deserves a special comment. Factor IX is probably not activated by thrombin , neither is it con-…”
supporting
confidence: 81%
“…Previous studies have shown that Macrogol does not influence the platelet level or the clotting system ). The development of thrombocytopenia was followed closely by samples obtained from the ear vein as described by Rapaport et al (1966). At the time of maximal thrombocytopenia, i.e., 12-16 days after the injections, a cannula was inserted in the femoral artery of all animals (Evensen et al 1967), and blood samples were taken to check the preparatory treatment.…”
Section: E X P E R I M E N T a L D E S I G Nmentioning
confidence: 99%
“…The elevated concentrations of thromboplastin in leukemic cells may explain the high incidence of generalized intravascular coagulation observed in acute promyelocytic leukemia [55,85,254] and in the course of leukemic cell destruction consecutive to chemotherapy [102]. It is well documented that infusions of tissue thromboplastin cause generalized intravascular coagulation [78,195,208,229]. It is understandable that patients suffering from leukemia or cancer may develop generalized intravascular coagulation, especially when tumor cells break down or are destroyed.…”
Section: Trigger Mechanism Of Generalized Intravascular Coagulationmentioning
confidence: 99%